JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF THE ONLINE STAY PERMIT SYSTEM FOR FOREIGNERS IN BATAM CITY - Nanda Horas Pranata; Fadlan; Ramon Nofrial (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Digital transformation in public services is an urgent need in realizing efficient and transparent governance, including in the field of immigration. The Directorate General of Immigration has implemented the Online Residence Permit Service System as part of the reform of residence permit services for foreign nationals. Batam City as a strategic area with high mobility of foreigners becomes an important locus in assessing the effectiveness of the system. This study is motivated by the importance of legal certainty, service efficiency, and protection of legal rights of foreign nationals in the process of applying for a digital residence permit. This study aims to analyze legal arrangements, implementation of online residence permit service system, as well as obstacles and solutions faced in improving the quality of immigration services in Batam City.The methods used are normative juridical and empirical juridical approaches with data collection techniques through document studies (secondary data) and interviews (primary data) with immigration officers, foreign service users, and other related parties.The results show that the online residence permit service system has a strong legal basis, but there are still gaps between regulations and practices in the field. The main obstacles include limited technological infrastructure, low user digital literacy, and suboptimal cross-sectoral coordination. In terms of implementation, this system has improved administrative efficiency, but has not fully guaranteed legal certainty and service satisfaction. It is recommended that the Directorate General of Immigration and Batam Immigration Office strengthen human resource capacity, improve infrastructure, prepare technical operational guidelines, and expand public education to service users. With these steps, the system is expected to run more effectively, adaptively, and in line with the principles of good administrative law.